Early Experiments on Meat in Near Infrared (NIR) Light - Swatland, Howard J. (European Journal of Applied Sciences, 2025)
Experiments with thin slices of meat showed that fat content is the dominant factor affecting NIR transmittance and reflectance. But beyond the peak wavelengths for fat detection, polarized NIR may also detect sarcomere length and pH-related aspects of meat quality, provided that the orientation of polarized NIR and muscle fibre orientation is controlled. The same relationships may be obtained from the surface of bulk meat using a combination of fibre optics with a graded index lens.